Why we should not cut off the king's head: ritual sovereignty and the "moral grammar" of the Thai State - Engelkamp, Stephan (Asien, 2015)
The idea of the sovereign state has often been theorized as a set of practices that evolved as a specifically European solution to the problem of difference. In order to further "provincialize" this perspective, my paper proposes to approach the topic through insights drawn from Governmentality Studies and from Social Anthropology. Doing this brings into view different notions of the state as embedded in a "moral grammar" that comprises both the social and the cosmological. Drawing on the work of Michel Foucault and Giorgio Agamben, the paper develops a theoretical framework that conceptualizes practices of governmentality in terms of contending valorizations of exchange systems. Hence, the state is incorporated into a totality of transactions that is concerned with the reproduction of the social and cosmic order and that transcends the traditional domain of secular politics. How these narratives are structured by ritual practices and embedded in a particular sociocosmological order is illustrated through a case study presented on the transformation of ritual politics in Thailand.